MODERASI BERAGAMA PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA NEGERI 1 KASIMAN KABUPATEN BOJONEGORO - Tri Setyo; Karjo; Santoso, Moch; Hakim, Ibnu (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2023)
Abstract Religious moderation, an attitude of mutual respect between religious communities, is very important to achieve harmony between religious communities, which ultimately will strengthen the unity of the nation and state. This research uses a descriptive qualitative research approach, with primary data sources of school principals, teachers and students as well as documents. The results of this research are (1) Planning for Religious Moderation of Students at Kasiman State Middle School 1, Bojonegore Regency, including: Student selection, Indoctrination includes: having noble morals and competitiveness, Instrumentation includes: written and well-organized practice (2) Implementation of Moderation The religion of students at Kasiman State Middle School 1, Bojonegoro Regency includes: an attitude of tolerance, not being a group fanatic, respecting culture, prioritizing unity. Well done